Assessing Children’s Islamic Value Development in Family Education: Development and Preliminary Psychometric Evaluation of a Parent-Reported Instrument - Yanti Karmila Nengsih; Friska Indria Nora Harahap; Ria Riza Alvi; Muhammad Adil; Arnady Arnady; Ahmad Syahid; Nurul Hayati; Betty Yulia Wulansari (Jurnal Pendidikan Islam, 2026)
Family education plays a central role in fostering children’s Islamic values. However, Islamic education research has paid limited attention to developing theoretically grounded measurement instruments for assessing these values from parents’ perspectives. This study aimed to develop and conduct a preliminary psychometric evaluation of a parent-reported instrument for assessing children’s Islamic value development within family education associated with Islamic schools. Grounded in an integrated framework combining Islamic Educational Philosophy, Ecological Systems Theory, Islamic Character Education, and Educational Measurement Theory, the instrument conceptualizes children’s Islamic values as a multidimensional construct encompassing emotional, social, economic, and religious dimensions. A quantitative survey design was employed involving 258 parents of children aged 2–12 years enrolled at Al Faruq Islamic School, Indonesia. Preliminary psychometric evaluation included corrected item–total correlation analysis and assessment of internal consistency using Cronbach’s alpha. Moreover, the findings indicated that 25 questionnaire items demonstrated satisfactory item discrimination, while the overall instrument exhibited good internal consistency (Cronbach’s α = .835). Descriptive findings further illustrated the instrument’s practical application, showing that parents strongly associated children’s Islamic value development with emotional cohesion and spiritual responsibility within family education. Moreover, this study contributes to Islamic education by providing a theoretically grounded framework, as well as a preliminarily evaluated parent-reported instrument for assessing children’s Islamic value development. To ensure the robustness of these findings, future studies should extend the instrument through broader validation involving more diverse populations and comprehensive psychometric analyses.